Associations between individual lower-limb muscle volumes and 100-m sprint time in male sprinters - Sugisaki, N.; Kobayashi, K.; Tsuchie, H.; Kanehisa, H. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To elucidate the relationship between the muscularity of individual lower-limb muscles and 100-m-race time (t100) in young-adult male sprinters. Methods: Thirty-one young-adult male sprinters took part in this study (age 19.9±1.4 y, height 173.5±4.6 cm, body mass 67.0±4.9 kg, t100 10.23-11.71 s). Cross-sectional images from the origin to insertion of 12 lower-limb muscles were obtained with via magnetic resonance imaging (MRI). The absolute volume of each muscle, the ratio of total volume of measured muscles to body mass, the ratio of individual muscle volume to body mass, and the ratio between 2 individual muscle volumes were calculated as indices of muscularity using the images. A stepwise multiple-regression analysis was performed to examine the association between the indices and t100. Results: A stepwise multiple-regression analysis produced an equation (adjusted R2=.234) with the gluteus maximus-to-quadriceps femoris muscle-volume ratio (ß=-0.509, P=.003) as the explanatory variable. Conclusions: Individual differences in 100-m-race performance cannot be explained by the muscularity of specific muscles, and 23% of the variability in the performance can be explained by the relative difference between the muscularity of gluteus maximus and quadriceps femoris; faster runners have a greater gluteus maximus relative to quadriceps femoris.